Exercício físico na doença pulmonar obstrutiva crônica estável: uma overview - Peixoto, Náthali de Mello (2022)
Chronic obstructive pulmonary disease (COPD) is a leading cause of morbimortality in the world. In non-pharmacological management of stable COPD, the application of physical exercise aims to improve functional capacity, Health-Related Quality of Life (HRQoL) and to relief limitating symptoms such as dyspnea. To elucidate the role of each exercise modality, this study aimed to provide an overview of systematic reviews (SR) assessing effects of aerobic exercise (AE), resistance exercise (RE), high-intensity interval training (HIIT) and inspiratory muscle training (IMT) compared to a non-exercise control group on outcomes of dyspnea, functional capacity and HRQoL. PubMed, Scopus, Cochrane Library, EBSCO and Web of Science databases were consulted, with 1500 records obtained. From these, only five SR were included, three of RE and two of IMT, none AE and HIIT SR met inclusion criteria for this study. Methodological quality was assessed by AMSTAR-2 tool. SR about RE provided significant improvements and favouring intervention group on dyspnea outcome and conflicting results regarding submaximal functional capacity (SFC). SR about IMT found significant improvements on dyspnea, SFC and HRQoL favouring intervention group, however no significant results were found for maximal functional capacity. These results allow to conclude the role of these two exercise modalities in reducing dyspnea in COPD patients and IMT effect to increase several outcomes, which emphasizes the inclusion of RE and IMT in rehabilitation programs for stable COPD.